Environmental status of Israel's Mediterranean coastal waters: Setting reference conditions and thresholds for nutrients, chlorophyll-a and suspended particulate matter. (April 2019) - Kress, Nurit; Rahav, Eyal; Silverman, Jacob; Herut, Barak
Abstract: Criteria for eutrophication related parameters to achieve and preserve good environmental status (GES) of the oligotrophic Israeli Mediterranean coast were proposed for nutrients, chlorophyll-a (Chl-a) and suspended particulate matter (SPM) concentrations. The criteria were derived from current conditions, the best choice for the area that has undergone large and irreversible ecological changes compared to the pristine background. A five-year data set (2010–2014, ca. 800 data points) was analyzed using statistical methods and best professional judgement. The coastal waters were divided into four provinces, data gaps were identified, and seasonal reference and threshold values for each province determined as the median and 1.5 times the median, respectively. Application of the derived criteria to data up to 2016 showed the coastal waters to be mainly in GES, with a few exceptions. Simplification of the proposed criteria for environmental management was addressed as well. Highlights: Environmental assessment criteria for eutrophication in the oligotrophic Israeli Mediterranean coast are presented. Reference and threshold values were derived from current conditions (2010–2014). Coastal water provinces were assessed for their present environmental status. Simplification of the criteria, for environmental management, is proposed.